Micro-computed tomography high resolution evaluation of dimensional and morphological changes of 3 root-end filling materials in simulated physiological conditions - Torres, Fernanda Ferrrari Esteves [UNESP]; Jacobs, Reinhilde; EzEldeen, Mostafa; Guerreiro-Tanomaru, Juliane Maria [UNESP]; dos Santos, Bernardo Camargo; Lucas-Oliveira, Éverton; Bonagamba, Tito José; Tanomaru-Filho, Mario [UNESP] (Springer Nature, 2020)
The aim of this study was to evaluate volumetric and morphological stability of 3 root-end filling materials in addition to porosity and interface voids, using micro-computed tomography (µCT) in high resolution and a highly accurate approach for image analysis. Following root-end resection and apical preparation, two-rooted maxillary premolars were divided into three groups, according to the filling materials: White MTA Angelus, Biodentine, and IRM. Samples were scanned by µCT at 5 µm after the setting time and at time intervals of 7 and 30 days after immersion in phosphate-buffered saline (PBS). Volumetric and morphological changes besides material porosity and interface voids were evaluated by comparing initial values and those obtained after immersion. Data were analyzed statistically, using ANOVA and t-tests (α = 0.05). All materials showed volumetric stability. Regarding the morphological changes, Biodentine had a significant thickness reduction after storage in PBS when compared with MTA. Biodentine also showed an increase in porosity, as well as in percentage and thickness of voids after 30 days of immersion. In conclusion, µCT in high resolution and an accurate image analysis approach may be used to evaluate morphological changes of endodontic materials. Although Biodentine showed suitable adaptability and lower values of porosity than MTA, after PBS immersion there was a dimensional reduction of this material, besides an increase in porosity and interface voids. [Figure not available: see fulltext.].